Research on the decision framework of an energy storage traction system plan for rail transit from the low-carbon perspective—based on the interval-value Pythagorean intuitionistic fuzzy environment - Lin, Lijun; Xu, Wenjie; Liu, Bo; Wang, Wenxuan; Zhao, Yulin; Tao, Min (Frontiers in Energy Research, 2023)
Low carbonization of the traction system is the key to low-carbon rail transit operation, and its preliminary plan decision plays a decisive role in whether low carbon can be achieved in later stages. Therefore, how to achieve scientific decisions of energy storage traction systems in a low-carbon background is a problem that needs to be solved. The innovation of this paper is as follows: first, aiming at the reality of the rail transit energy storage traction system, a decision index system of the energy storage traction system which contains seven attributes and 18 criteria is constructed; second, aiming at the uncertainty of decision information and the decision makers’ aversion to risk, the decision model adapted to the energy storage traction system decision is constructed based on the interval Pythagorean intuitionistic fuzzy number and VIKOR model principle. The decision index system and decision model together constitute the decision framework. The case study results show that the decision index system can provide scientific guidance for the decision of the energy storage traction system, and the decision model can provide risk aversion type decision results with good robustness.